Effect of Plectranthus amboinicus, Lour. Spreng. n-Hexane Extract on T47D Cells Line: Proliferation, Apoptosis and Itâ€™s Combination with Doxorubicine - Zaitun Hasibuan, Poppy Anjelisa; Rosidah; Nasution , Pandapotan; Ilyas , Syafruddin (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
The objectives of the study are to investigated the growth-inhibiting and apoptosis mediating effect of Plectranthus amboinicus (Lour.) Spreng n-hexane extract (PANE) on T47D cell lines. The assays were performed in the study were cytotoxicity assay and apoptosis induction of T47D cells. The cytotoxicity effects were determined by using MTT [3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide] assay. The effect of apoptosis were observed by ethidium bromide-acrydine orange method. The growth of T47D was inhibited by treatment with PANE on concentrations 20; 40; dan 80 Âµg/mL. The cell death (apoptosis) induced by PANE was characterized by orange fluorescent on the IC50 concentration. These results concluded that the n-hexane extract of Plectranthus amboinicus, (Lour.) Spreng. inhibited the growth of T47D breast cancer cells in dose and time dependent manners. PANE also could induced apoptosis on T47D breast cancer cells, but the combination of PANE-doxorubicine did not show the synergistic effect. The results suggesting that PANE may be a potent agent for the chemoprevention of breast cancer.